1993
DOI: 10.1111/j.1540-8191.1993.tb00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocardial Dissecting Hematoma: An Unusual Form of Subacute Cardiac Rupture

Abstract: Intramyocardial dissecting hematoma following myocardial infarction is an unusual form of subacute cardiac rupture that tends to develop along naturally occurring dissection planes between the spiral muscles of the ventricle. The diagnosis has commonly been made at surgery, postmortem examination, or by echocardiography. Most are associated with acute transmural inferior infarction. Few patients survive without surgical intervention. Fourteen cases have appeared in the literature. One additional case is descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 24 publications
(14 reference statements)
3
62
0
3
Order By: Relevance
“…In addition, computed tomography of the chest and cardiac magnetic resonance imaging can have diagnostic roles in revealing intact myocardium around an intramyocardial cavity. 2,3 In our patient, we first identified intramyocardial hematoma by echocardiography and confirmed that diagnosis by means of computed tomography. …”
Section: Commentsupporting
confidence: 70%
“…In addition, computed tomography of the chest and cardiac magnetic resonance imaging can have diagnostic roles in revealing intact myocardium around an intramyocardial cavity. 2,3 In our patient, we first identified intramyocardial hematoma by echocardiography and confirmed that diagnosis by means of computed tomography. …”
Section: Commentsupporting
confidence: 70%
“…Между тем у взрослых формирование гематомы МЖП описано после инфарктов миокарда (ИМ) [2,10], операций хирургиче-ской и чрескожной реваскуляризации миокарда [4], есть наблюдения посттравматической гематомы МЖП [11,12].…”
unclassified
“…This entity can develop after blunt chest trauma (4), but is usually the consequence of acute myocardial infarction. The chance of survival is thought to be low if corrective surgery is not performed (3). On the other hand, in some cases a spontaneous resolution of the pseudo-pseudoaneurysm was also detected (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…It is extremely rare that an incomplete rupture of the infarcted left ventricular wall is reported. In this condition-which is termed intramyocardial dissecting hematoma or pseudo-pseudoaneurysm-the rupture of the myocardium remains circumscribed within the ventricular wall itself, freely communicating with the left ventricular cavity (2,3). This entity can develop after blunt chest trauma (4), but is usually the consequence of acute myocardial infarction.…”
mentioning
confidence: 99%